Applications Of Red Onion Skin Extract (Allium cepa L.) On The Growth And Years Of Peanuts (Arachis hypogaea L.) - Hakiki, Iqmal; Adnan; Haryuni; Eko Fransisko (Jurnal Agricultural Science, 2023)
ABSTRACT : Groundnut (Arachis hypogaea L.) is one of the most widely cultivated commodities by farmers in Bengkulu Province after rice, cassava, corn, sweet potatoes and soybeans. The amount of peanut production in Bengkulu Province can be increased by increasing the area of ​​land and increasing productivity through the use of superior seeds and good care. The harvested area of ​​peanuts in Bengkulu Province in 2014 reached 4,535 ha with a total production of 4,612 tonnes (BPS 2015). Increasing the amount of production and harvested area will also increase the number of peanut products offered. This research was conducted from August to November 2022 at the Planting House of Pat Petulai University, Dwi Tunggal Village, Curup District, Rejang Lebong Regency, Bengkulu Province, with an altitude of 620 meters above sea level. The method used in this study was a completely randomized design (CRD) which consisted of 4 treatment levels. The results of the analysis of variance in the treatment of shallot skin extract did not have a significant effect on the variable number of flowers, number of leaves, and plant height. While the treatment of shallot skin extract had a significant effect on the variable number of pods (7.15 pods) and fresh weight (8.6 grams). The treatment of shallot skin extract had a very significant effect on dry weight (15.19 grams). The application of shallot skin extract effectively increased the yield of peanut plants, because it increased the number of pods, fresh weight, and dry weight of plants. At a concentration of 45 ml/liter of water, shallot skin extract gave the best results on the variable number of pods and fresh weight on the growth and yield of peanuts. Based on the results of research that has been conducted regarding the application of shallot skin extract to the growth and yield of peanut plants, the authors suggest the use of shallot skin extract at a concentration of 45 ml/liter of water in peanut cultivation in areas with an altitude of 620 meters above sea level.